Strengthening of Social Cohesion in the Practice of Liké Geleng among the Aneuk Jamè Ethnic Group in Aceh - Abubakar, Bustami; Ikhwan, Ikhwan; Sugiarso, Sugiarso (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2021)
This study discusses the implementation of liké geleng and its relationship with strengthening social cohesion among the Aneuk Jamè ethnic group in Kampung Balai, Samadua, South Aceh. The research objective is to find a link between the implementation of liké geleng and the strengthening of social cohesion in the Aneuk Jamè ethnic community. This research uses a qualitative approach. The informants consisted of religious leaders, traditional leaders, women leaders, and the community involved in carrying out the Maulid Nabi memorial in the village. The results of the study concluded that the implementation of liké geleng among the Aneuk Jamè ethnic group as an activity in commemoration of the Maulid Nabi Muhammad SAW is an activity that can strengthen social cohesion among the community. This is indicated by the development of closer friendship and kinship, increasingly frequent social interactions, and stronger cooperation between communities.